Admission test as a screening test for fetal distress in labour - Rao, Smitha B.; D’Souza, Reena; Sherigar, Bhavana; R, Soumya; Kaveri, Vismaya; Singh, Anamika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: This study was undertaken with the purpose of evaluating the efficacy of labour admission test as a screening test to identify the compromised fetus or fetus at risk and to correlate with perinatal outcome. Methods: This was a retrospective cohort study of 300 patients in 1st stage of labour admitted to labour room at tertiary care hospital over a period of one and a half years. Patients with Singleton pregnancy, Cephalic presentation & Gestational age beyond 34 weeks were included in this study. A BPL electronic foetal heart monitor was used to perform the admission test. With the patient in left lateral position a 20 minute continuous electronic recording (paper speed of 3 cm per minute) of foetal heart rate and uterine activity was obtained, on a cardiotocograph. Results: Statistical significance was calculated between different categories for different parameters too. A p value of of<0.05 was considered to be statistically significant. Fetal distress was seen 64.71% in Category III group 33.33% with Category II group and 4.74 % in Category I trace. admission test has 97.75% specificity and 95.5% negative predictive value. Conclusions: Admission test makes screening convenient. Since it is non-invasive, patients also cooperate. Admission test helps to plan subsequent management of labour. It is a good predictor of foetal well-being at the time of admission and for the next few hours.